Colocasia esculenta stems for the isolation of cellulose nanofibers: a chlorine-free method for the biomass conversion - Dominic, C. D. Midhun; Maheswary, S.; Neenu, V. K.; Sajadi, S. Mohammad; Rosa, Derval dos Santos; Begum, P. M. Sabura; Mathew, Mariya; Ajithkumar, T. G.; Parameswaranpillai, Jyotishkumar; George, Tresa Sunitha; Resmi, V. C.; Ilyas, R. A.; et al. (Biomass Conversion and Biorefinery, 2024)
The reuse of waste products is the green key to sustainability. The extraction of cellulose nanofibers from Colocasia esculenta stems is presented in the paper. The study proved that the waste biomass could be effectively re-engineered into highly valued cellulose nanofibers (CNFs). Cellulose nanofibers were extracted via a chemo-mechanical route. The pre-treatments included mild alkali hydrolysis (2% NaOH) and chlorine-free bleaching (peroxide bleaching in an alkaline medium). Cellulose I-beta structure was confirmed using C-13 solid-state nuclear magnetic resonance spectroscopy and X-ray diffraction analysis. The elemental analysis of CNFs detected the elements, carbon and oxygen. The CNFs had a crystallinity and transmittance of 71.72% and 60%, respectively. Microscopic studies verified the elimination of non-cellulosic components and the fibrous nature of CNFs. Moreover, the fiber diameter of CNFs was 20-40 nm. Thermal analysis revealed good thermal stability of 335.8 degrees C (T-50) for nanofibers. Long-term aids are numerous in eco-friendly technology. Developing an eco-design will support zero waste ideals, lowers carbon dioxide emissions, and encourages a circular economy. Owing to the merits of natural fibers, they can be adopted in various sectors including packaging, automobile, aerospace, electronics, biomedical, construction, and furniture.
Keywords: acid hydrolysis; cellulose nanofibers; Colocasia esculenta stems; High crystallinity